18.9k views
5 votes
PLEASE HELP ME!!! (20 POINTS im giving it away in a smaller amount because im becoming poor from giving them away)

PLEASE HELP ME!!! (20 POINTS im giving it away in a smaller amount because im becoming-example-1
User Ford
by
5.8k points

2 Answers

4 votes

Answer:

Yeah what she said

Explanation:

User Thunderstick
by
6.3k points
4 votes

The right side of the equation can be rewritten in terms of p as 4p (4p = 4(x^2 +6) = 4x^2 +24)


Now you have (x^2 +6)^2 - 21 = 4p

Replace (x^2 +6) with p

p^2 - 21 = 4p

Subtract 4p from each side:

p^2 - 21 -4p = 0

Rewrite the expression to get p^2 - 4p -21 = 0


User Mahinlma
by
6.0k points